The Inspection of Gendered Language in the Reporting of Olympic Games in The Star / Marlina Jamal - Jamal, Marlina (Universiti Teknologi MARA, Kedah, 2015)
This paper examines the language used by The Star newspaper in the representation of women athletes in the coverage of the 2008 Beijing Olympics. The purpose of this study is to decode the projection of women athletes through the analysis of specific linguistic features. To achieve this purpose, a Critical Discourse Analysis approach is carried out on 17 articles published in The Star from 9th August 2008 to 22nd August 2008. Fairclough’s three-dimensional framework, together with Halliday’s Systemic Functional Linguistics approach is used for the purpose of analyzing the data. The linguistic features analyzed are vocabulary, transitivity, passivization, nominalization and also features of intertextuality such as direct quotes and also scare quotes. The findings show that all the linguistic elements analyzed act as cues to reveal the ideological slant of the newspaper. Woman athletes are portrayed in a way that promotes gender discrimination, whereby many negative aspects such as limited physical capability, sexualization of female athletes and also underestimating their achievements occur immensely in the newspaper reports analyzed. Woman athletes are constructed as inferior in almost all occasions. It is disheartening to know that despite efforts taken by government and non-government organizations to address discrimination and inequalities in sports, gender discrimination still exists. More strategies must be taken to address the biased portrayal of women athletes in the media, especially newspaper. So, the press must be more transparent in the reporting of news and stop the stereotypical representation of women in sports. Attention should be paid not only to reduce the sexualized representation, marketing and promotion of women’s sport, but also changing the dominant stereotypical gender images to reflect the progress towards gender equality in sports.